Pemberdayaan Kader Posyandu dalam Pelaksanaan Program Posyandu Menuju Indonesia Sehat - Ayunil Ummi; Arifah Yenni Gustia; Hermawati Hermawati; Sakinah Sakinah; Rahima Zakia; Wanda Fitri; Hummaira Hutagaol (Universitas Islam Negeri Imam Bonjol Padang, 2026)
Participation in the community towards a Healthy Indonesia is an important pillar in realizing it. Without community involvement, it will be difficult to achieve, because in essence the goal of a healthy Indonesia is the desire of all parties. Posyandu cadres are part of the community who are willing to play an active role in the activities of the Integrated Service Post, commonly called Posyandu. The participation of Posyandu cadres is a potential of the community that will be managed well. The purpose of this study is to describe and understand the participation of Posyandu cadres in Jorong Irian Nagari Ujung Gading, Lembah Melintang District, West Pasaman Regency. This study is a descriptive qualitative study. Describes how the participation of Posyandu cadres in the success of the implementation of Posyandu activities by providing basic health and social services for the community such as infants, toddlers, pregnant women and the elderly. The findings show that the participation of Posyandu cadres in towards a healthy Indonesia in Jorong Irian Nagari Ujung Gading is due to good communication patterns and strong emotional relationships.